The role of strategic planning in the organization of management systems in higher education institutions: insights from international practice - Khalilov, Taleh; Adilzade , Inci; Rzayev, Oktay; Guliyev, Nizami; Yusifova, Nezaket (Edelweiss Applied Science and Technology, 2024)
Strategic planning has become a cornerstone of effective management in higher education institutions (HEIs), enabling them to navigate the complexities of a dynamic global environment. This paper explores the critical role of strategic planning in the organization of management systems within HEIs, drawing on international practices to highlight its impact. Key topics include the foundational principles of strategic planning, common challenges faced by institutions, and best practices for overcoming these obstacles. The study emphasizes the necessity of data-driven decision-making, inclusive stakeholder participation, and continuous evaluation to achieve institutional resilience, academic excellence, and sustainable development. By synthesizing global experiences, this research provides actionable insights for HEIs seeking to align their strategic objectives with both local and global demands.